4CPS-252 Effectiveness of sacral neuromodulation in two patients with tethered cord syndrome outputs: a case report. (2nd March 2018) - Inserra, C; Scalzi, V; Destro, F; Riccipetitoni, G; Zovi, A; Zampogna, L; Zerega, G
Abstract : Background: The Tethered Cord Syndrome (TCS) is the clinical manifestation of a neurological disorder caused by the caudal anchor of the marrow that limits movement within the spine. Ischaemic injury from stretching may result in neurological, urinary and intestinal disorders. The neurological bladder requires pharmacological therapy, intermittent catheterisation and surgical treatments to achieve urinary continence and save renal function. Sacral neuromodulation (NMS) is an innovative treatment option that uses the electrostimulation of the roots of the sacral nerves that are responsible for modulation of the bladder and the intestinal-emptying function. The neurostimulator sends small electrical impulses (regulation of electrical impulses is possible) to the sacral nerve through the lead, closely located. Purpose: To describe the short-term results of NMS in two adolescents with neurological bladder and neurogenic constipation, refractory to intensive conservative treatment. Material and methods: O. G.: 11-years-old (TCS outcome and anorectal malformation) undergoes NMS. During the 30 days' trial, improved intestinal function by reducing the number of intestinal washings two to three times per week (versus 7/7). Partial improvement of urinary function with spontaneous urination (five to six times per week). G. S.: 14-years-old, patient with neurological bladder and neurogenic constipation (TCS outcome), sometimes suffering from urinary incontinence. Undergoes NMS. During the 30 days' trial, there has been a clinical improvement, with the disappearance of urinary incontinence, perception of the stimulus (twice per day) and spontaneous urination (once per day). Results: In both patients, urodynamic examination showed an improvement in bladder compliance, even without the use of drug therapy. NMS was associated with patients' and stakeholders' perception of overall success and positive impact on quality of life. From an economic perspective, the cost of interventions (€9, 920/intervention) was compensated by the reimbursement fees of Diagnosis-Related Groups (DRG). Conclusion: NMS seems to be a promising and sustainable new treatment option for adolescents with neurological bladder and neurogenic constipation. However, more randomised, long-term follow-up studies are required to definitely confirm this conclusion. No conflict of interest